Karakteristik Hitung Jumlah Sel Leukosit Pasien Demam Tifoid yang Dirawat di RSU Martha Friska Multatuli Medan - Jenny Ria Sihombing; Helena Rugun Nauli Nainggolan; Nathalia Elizabeth Rouli Sipahutar; Sarah Elisabet Siagian (Malahayati Nursing Journal, 2024)
ABSTRACT Typhoid fever is an acute infection of the digestive tract caused by Salmonella typhi. Typhoid fever is still a global health problem for people around the world, especially in developing countries. Infection that occurs in typhoid fever can cause a decrease in neutrophil production so that laboratory results can show neutropenia. Leukopenia is a decrease in the number of white blood cells in peripheral blood which can occur due to a decrease in the number of one type of leukocyte which is generally caused by a decrease in neutrophils (neutropenia). Research entitled Characteristics of Leukocyte Cell Counts in Typhoid Fever Patients Treated at RSU Martha Friska Multatuli Medan. The aim of the research was to determine the number of leukocyte cells in typhoid fever sufferers treated at RSU Martha Friska Multatuli Medan. This research uses an analytical research design with a cross sectional method, in May - August 2023. From the results of research conducted at the Laboratory of RSU Martha Friska Multatuli Medan in 2023 on 30 people suffering from typhoid fever who were treated at the Martha Friska Multatuli Hospital, it was found that they were aged 0-12 years old as many as 4 people (13%), aged 13-18 years as many as 8 people (26%) and aged ≥ 19 years namely 18 people (61%). There were 12 men (60%) and 8 women (40%). The largest number of jobs were students, 17 people (57%). The results of the examination showed that 13 patients (44%) had an increased leukocyte cell count (leukocytosis), 10 people (33%) had a normal leukocyte count and 7 people (23%) had leukopenia. It was found that 20 typhoid fever patients experienced neutrophilia (67%), 2 people had neutropenia (7%), 8 people had normal neutrophils (26%), while 1 person (3%) had typhoid fever patients who experienced lymphopenia. (57%) and normal lymphocytes in 12 people (40%). Keywords: Leukocyte Cell Count, Patient, Typhoid Fever  ABSTRAK Demam tifoid adalah infeksi akut pada saluran pencernaan yang disebabkan oleh Salmonella typhi. Demam tifoid masih menjadi masalah kesehatan global bagi masyarakat dunia, terutama di negara yang sedang berkembang. Infeksi yang terjadi pada demam tifoid dapat menyebabkan penurunan produksi neutrofil sehingga pada hasil laboratorium dapat ditemukan neutropenia. Leukopenia merupakan penurunan jumlah sel darah putih dalam darah perifer yang dapat terjadi karena berkurangnya jumlah salah satu jenis leukosit yang umumnya disebabkan oleh penurunan neutrofil (neutropenia). Penelitian dengan judul Karakteristik Hitung Jumlah Sel Leukosit Pasien Demam Tifoid yang dirawat   di RSU Martha Friska Multatuli Medan. Tujuan penelitian utukmenentukan jumlah sel leukosit pada penderita demam tifoid yang dirawat di RSU Martha Friska Multatuli Medan. Penelitian ini menggunakan disain penelitian analitik dengan metoda cross sectional, pada bulan Mei – Agustus 2023. Dari hasil penelitian yang dilakukan di Laboraturium RSU Martha Friska Multatuli Medan Tahun 2023 pada 30 orang penderita Demam tifoid yang dirawat di RS Martha Friska Multatuli didapatkan usia 0-12 tahun sebanyak 4 orang (13%), usia 13-18 tahun sebanyak 8 orang (26%) dan usia ≥ 19 tahun yaitu 18 orang (61 %). Jenis kelamin laki-laki sebanyak 12 orang (60%) dan perempuan sebanyak 8 orang (40%). Pekerjaan terbanyak adalah pelajar sebanyak 17 orang (57%). Didapatkan hasil pemeriksaan pasien dengan jumlah sel lekositnya meningkat (leukositosis) sebanyak 13 orang (44%), jumlah leukosit normal sebanyak 10 orang (33%), dan leukopenia sebanyak 7 orang (23%). Didapatkan pasien demam tifoid yang mengalami netrofilia sebanyak 20 orang (67%), neutropenia 2 orang (7%), netrofil normal 8 orang (26%), sedangkan pasien demam tifoid yang mengalami limfositosis sebanyak 1 orang (3%), limfopenia 17 orang (57%) dan limfosit normal 12 orang (40%). Kata Kunci: Jumlah Sel Leukosit, Pasien,  Demam Tifoid